Potensi Perguruan Tinggi Islam Sebagai Lembaga Ijtihad Jama’i - Hamsyah, Junaidi (Universitas Islam Negeri Raden Intan Lampung, 2016)
The responsibility of moslem to translate the holy Qur’an and Hadist as the aswers to all life problematics is in the hands of intelectual moslem. Islamic universities are formal institutions that not only play a role in education but also have the potential to become the most authoritative da'wah institution to issue legal decisions. Academic community are individuals who have been equipped with adequate tools of ijtihad, that is comprehensive and holistic science disciplines. Islamic universities, moreover, have qualified to become ijtihad jama'i institutions that are needed by modern Muslims.Tanggung jawab umat Islam untuk menerjemahkan Alquran dan Hadist sebagai jawaban segala problematika hidup ada di tangan muslim intelek. Perguruan tinggi Islam adalah lembaga formal yang tidak hanya berperan dalam pendidikan, namun juga berpotensi menjadi institusi dakwah paling otoritatif untuk mengeluarkan keputusan hukum. Komunitas akademis adalah individu yang telah dilengkapi dengan peralatan ijtihad yang memadai, yaitu disiplin sains yang komprehensif dan holistik. Universitas Islam, apalagi, telah memenuhi syarat untuk menjadi ijtihad institusi jama'i yang dibutuhkan oleh umat Islam modern. Kata kunci: perguruan tinggi, ijtihad jama’i, modernitas.